Media Pembelajaran Video Animasi Meningkatkan Kemampuan Menulis Teks Berita Siswa Sekolah Menengah Pertama - Pratama, Despita (Universitas Pendidikan Ganesha, 2025)
The learning activity of writing news texts also only uses textbooks. This causes students to have difficulty aligning one sentence with another. Based on this, the purpose of this study is to analyze the effect of animated video learning media on the ability to write news texts of junior high school students for grade VII students. This type of research uses a quasi-experimental method using two classes of research samples. The treatment design in this study is a control group posttest-only design. The population is grade VII junior high school students, totaling 252 students. In this study, two classes of samples were used so that the total sample was 84 students. The data collection method was carried out by giving tests and documentation. The data analysis technique used t-test statistical analysis. The results of the study showed that the average value of the experimental class was greater than the average value of the control class. The average value of the experimental class given treatment, namely using animated video learning media, was 74.5. The average value of the control class that did not use animated video media was 66.07. The results of the hypothesis test showed that there was an effect of animated video learning media on the ability to write news texts of grade VII junior high school students. It was concluded that animated video learning media can improve the news writing skills of seventh-grade junior high school students. The implication of this research is that animated video learning media can be used to improve the news writing skills of junior high school students.